1996
DOI: 10.1007/bf00029058
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter and the indigenous nitrogen supply of intensive irrigated rice systems in the tropics

Abstract: Soil organic matter (SOM) has been proposed as an index of N supply in paddy soils although field validations are few. We evaluated the relationship between the indigenous N supply (Ni) of the soil-floodwater system and soil organic carbon (SOC) or total N (Nt) in surface soil of long-term fertility experiments (LTFEs) at 11 sites, in 42 farmer's fields with similar soil type, and in the same field in ten consecutive rice (Oryza sativa L.) crops. The Ni was estimated by crop N uptake from plots without applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 34 publications
(19 reference statements)
5
60
2
1
Order By: Relevance
“…It has been reported that soils with less than 0.07% total N will have limited N mineralization potential, while soils with >0.15% total N would be expected to mineralize significant amount nitrogen during the following crop cycle (Kamiri et al, 2013;Cassman et al, 1996;Becker et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that soils with less than 0.07% total N will have limited N mineralization potential, while soils with >0.15% total N would be expected to mineralize significant amount nitrogen during the following crop cycle (Kamiri et al, 2013;Cassman et al, 1996;Becker et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Espe et al [18] estimated a linear effect of 1.44 kg/ha for every g/kg increase in SOC for rice on organic soils. However, Cassman et al [30] observed a poor correlation between indigenous N supply and SOC in the rice systems, and attributed the N content to the N inputs from sources other than SOM mineralization, degree of congruence between soil N supply and crop demand, and differences in SOM quality. Obviously, the N supply from SOM mineralization would vary substantially, and it should be incorporated into other fertilization recommendation strategies such as site-specific nutrient management in a given region having similar soil properties, climate, and crop management [18].…”
Section: Discussionmentioning
confidence: 99%
“…The total accumulation of N by rice in the absence of fertilizer N has increasingly been used as a fi eld-based measurement of soil N supply, referred to as soil N-supplying capacity (SNSC) or indigenous N supply (INS) (Olk et al, 1999b;Dobermann et al, 2003). Studies in the 1990s, highlighted the high spatial and temporal variability associated with fi eldmeasured INS, based on total accumulation of N by rice in zero-N plots (Cassman et al, 1996b). Field-measured INS is oft en not correlated with SOM, laboratory measurements of soil N availability, or fi eld measurements of inorganic soil N (Cassman et al, 1996b;Adhikari et al, 1999), and even when relationships exist, the measured soil parameters explain only a small portion of the variation in rice yield in zero-N plots (Yadav, 2003).…”
Section: Mineralization and Immobilizationmentioning
confidence: 99%